StL Model Implementation, Challenges, and Can Be Implemented; Case in urban and rural school in Sintang District - Muhammad Iqbal Ripo Putra (Jurnal Pendidikan Bahasa, 2021)
This study aims to develop a model to improve the quality of StL schools this is to ensure that it can be applied at schools in Sintang Regency under the challenging needs and potentials they have, based on the school perspective. The result of this study was expected to provide description of the How far has the activities included in StL model been applied by school, what challenges did urban and rural schools face in implementing the activities of StL model, how is StL model which could be apply in urban and rural schools locally and contextually. This research was multiple case study which was conducted by using a descriptive qualitative approach involving 4 schools spread across Sintang Regency, namely in rural and urban areas. In this case, the 4 schools are middle schools which include 2 different districts, namely Sintang District and Sepauk District. The technique of data collection used in this research was direct communication in the form of semi-structured-interview and the tool was interview guidance. The data analysis used in this research was descriptive qualitative, using thematic analysis and cross case analysis techniques. The result of this study was recommendation for improving the application of StL model been applied by considering which StL model that could be apply locally, contextually and the challenges found by schools in implementing StL model.